Human ventilatory response to 8 h of euoxic hypercapnia. - Tansley, J; Pedersen, M; Clar, C; Robbins, P (1998)
Ventilation (VE) rises throughout 40 min of constant elevated end-tidal PCO2 without reaching steady state (S. Khamnei and P. A. Robbins. Respir. Physiol. 81: 117-134, 1990). The present study investigates 8 h of euoxic hypercapnia to determine whether VE reaches steady state within this time. Two protocols were employed: 1) 8-h euoxic hypercapnia (end-tidal PCO2 = 6.5 Torr above prestudy value, end-tidal PO2 = 100 Torr) followed by 8-h poikilocapnic euoxia; and 2) control, where the inspired gas was air. VE was measured over a 5-min period before the experiment and then hourly over a 16-h period. In the hypercapnia protocol, VE had not reached a steady state by the first hour (P < 0.001, analysis of variance), but there were no further significant differences in VE over hours 2-8 (analysis of variance). VE fell promptly on return to eucapnic conditions. We conclude that, whereas there is a component of the VE response to hypercapnia that is slow, there is no progressive rise in VE throughout the 8-h period.